Population toxicokinetics of ethylene: Calibration and preceding investigations - Barbara Quinke; Silvia Selinski; Klaus Golka; M. Blaszkewicz (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2000)
A basic step in the risk assessment of potential carcinogens is the determination of toxicokinetic parameters. The present approach is part of a strategy to determine the processes of uptake, elimination, and metabolism of the gas ethylene, an important industrial chemical, which is classified in category 3 of carcinogenic substances in the German list of MAK- and BAT-values. This paper deals with the calibration, which is indispensable to determine the decline of atmospheric concentrations of ethylene within a broad range of initial concentrations applied in an inhalation experiment.
Keywords: 519; Ethylene; ethylene oxide; calibration; population toxicokinetics; risk assessment